(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
Gastrointestinal parasitism and anthelmintic efficacy are of global concern for livestock and public health. An investigation on cattle gastrointestinal parasites and anthelmintic efficacy was conducted at Fulbaria Upazila, Mymensingh in 2017. Out of 100 fecal samples examined using simple sedimentation method, 70% cattle were found positive for parasites. The identified parasites were Paramphistomum spp. (27%), Fasciola gigantica (15%), Schistosoma spp. (10%), Haemonchus spp. (14 %) and Balantidium coli (12%). No significant variation was found in the prevalence rate between young (<2 years) and adult cattle (≥ 2 years). Significantly higher infection rate was recorded in male (81.63%) and in poor body conditioned animals (95.83%). For anthelmintic efficacy, feces from 50 animals were screened for eggs per gram (EPG) using McMaster technique. Twenty four cattle (>200 EPG) were allotted equally into three groups and further treated with either albendazole or ivermectin or kept as untreated control. EPG were again estimated for those animals at 14 days post-treatment. Status of anthelmintic efficacy was determined by using the fecal egg count reduction percentage (FECR %) test. The FECR % for albendazole and ivermectin were 98.76% and 95.01%, respectively. Results from this study indicated high parasitism in the study area and relatively higher efficacy of albendazole compared to ivermectin. Further studies are necessary to rule out the possibilities of anthelmintic resistance to parasites in cattle throughout the country as early as possible with a view to increase farmer awareness and to develop effective control strategies against endoparasites. Vol. 9, No. 3, December 2022: 289-297